Cultural Codes of Society: Scientific and Practical Significance in Modern African Studies - MOSEIKO Aida Nikolaevna (Ученые записки Института Африки Российской академии наук)
The article is devoted to the topic of searching for cultural codes. It presents the author’s approach to understanding the place and role of the problem of cultural codes in modern studies of Africa. The article presents an overview of the main options for understanding and defining cultural codes from the standpoint of both theoretical-rational and empirical-intuitive approaches. The relevance of the topic of cultural codes is considered in two aspects: from the point of view of contribution to the scientific development of the problems of cultural codes as an interdisciplinary problem and from the point of view of solving the practical task of increasing the effectiveness of the system of Russian-African relations based on mutual understanding and mutual respect of partners.